Malay medical manuscripts: heritage from the garden of healing - Mohd Shafri, Mohd Affendi (Akademi Jawi Malaysia, 2017)
The Malay Archipelago is like a garden rich in plants, animals, and minerals of medicinal benefits. The healing tradition of the Malays utilises these resources, and Malay medical practitioners documented their uses alongside descriptions of diseases in many manuscripts still extant today in libraries, institutions and personal collections. This volume presents a collection of arcticle by researchers acros several differing fields of specialities to give a multidisciplinary view of Malay medical manuscripts - the different texts, their contents, and their socio-intellectual significance. Thus, a philologist or a historian will be excited to read this volume, as much as a modern doctor, dentist, pharmacist, and scientist would find it relevant to their work. The knowledge of the Malays in medicine is centuries old, and the study of their wisdoms, contained in their oral as well as written heritage, is important to appreciate the past and to creat the future.